Evaluation of COLIA1 gene rs1107946 polymorphism in relation to bone mineral density and fracture risk in Slovak postmenopausal women - Boroňová, Iveta; Mathia, Matúš; Mačeková, Soňa; Bernasovská, Jarmila; Gaľová, Jana (Central European Journal of Public Health, 2023)
OBJECTIVES: The aim of the study was the evaluation of the rs1107946 polymorphism of the COLIA1 gene impact on bone mineral density and fracture risk in Slovak postmenopausal women. METHODS: One hundred and twenty-seven postmenopausal Slovak women with a diagnosis of osteopenia/osteoporosis were genotyped for rs1107946 polymorphism of the COLIA1 gene. Clinical and anthropometric data were obtained. DNA isolation was performed using a standard protocol. Genetic analyses of the rs1107946 polymorphism of the COLIA1 gene were performed by the TaqMan SNP genotyping assays. RESULTS: The study confirmed a statistically significant relationship using an association analysis between the rs1107946 polymorphism of the COLIA1 gene genotypes and body weight of the Slovak postmenopausal women with osteopenia/osteoporosis (p = 0.03). The study revealed a significant association of the risk T allele of the rs1107946 polymorphism of the COLIA1 gene with osteoporotic fractures (p = 0.038). The odds ratio confirmed 2.060 times higher risk of osteoporotic fractures in Slovak postmenopausal women with the presence of risk T allele of the rs1107946 COLIA1 gene polymorphism (OR = 2.060; 95% CI: 1.024-4.144). CONCLUSION: The results of this study revealed an association of T allele of the rs1107946 COLIA1 gene polymorphism with osteoporotic fractures in Slovak postmenopausal women with osteopenia/osteoporosis and suggest that the rs1107946 polymorphism of the COLIA1 gene may be a molecular biomarker usable in the management of osteoporosis.
Keywords: Postmenopause; osteoporóza; Humans; osteoporotické fraktury; Genotype; Slovakia; postmenopauza; Osteoporosis; Polymorphism, Genetic; Slovenská republika; polymorfismus genetický; postmenopauzální osteoporóza; Osteoporotic Fractures; Osteoporosis, Postmenopausal; kostní denzita; ženské pohlaví; genotyp; lidé; Bone Density; Female